Meeting Energy Concept Targets for Residential Retrofits in Germany: Economic Viability, Financial Support, and Energy Savings - Karsten Neuhoff; Hermann Amecke; Kateryna Stelmakh; Anja Rosenberg; Aleksandra Novikova (Climate Policy Initiative, 2011)
In the 2010 Energy Concept, the German government committed to reducing the primary energy requirement of buildings by 80% by 2050 and to increase the thermal retrofit rate from 0.8% to 2% per year. The 2% target is less than the 3%1 rate at which outer walls are currently being renovated each year, so it is achievable even if the government only targets buildings that are already planning a renovation. If a 2% retrofit rate were achieved, most German buildings would have thermal retrofits by 2050. However, in order to achieve the 80% reduction of the primary energy requirement in the building sector, each thermal retrofit has to be ,,deep‟; that is, it must reduce the energy requirement by around 80%. This paper addresses three questions this raises: 1. What are the costs of deep thermal retrofit for the owner of the building? Is it economically viable? 2. What scale of financial support will be required if the thermal retrofit rate increases to 2% per year? 3. How much energy could be saved?
Keywords: H31; R38; Q48; 330; thermal retrofit; incremental costs; financial support; Energy efficient building; Subsidy